Marketing Strategies of CV. Kopi Panas Event Organizer Bali in Enhancing Brand Awareness - Komang Pandini Niken Absari Komang; I Gusti Ngurah Agung Suprastayasa; I Putu Esa Widaharthana (Jurnal Pariwisata Nusantara (JUWITA), 2024)
Purpose: This study examines the 7P marketing strategies of CV. Kopi Panas Event Organizer Bali in enhancing brand awareness. The issues faced include intense competition and a lack of innovation in services and promotions. The objective is to identify and implement effective marketing strategies to boost brand awareness. Method: This study employs a qualitative approach through interviews with vendors, clients, and event organizers, as well as SWOT analysis. Data was collected and analyzed using thematic analysis and SWOT techniques. Result: The results of the study indicate that CV. Kopi Panas has implemented various marketing strategies, including product development, pricing review, diversification of event locations, promotion optimization, team skill development, process efficiency improvement, and physical facility maintenance. These strategies have helped the company enhance brand visibility and market competitiveness. However, further adjustments are needed in digital promotion and product innovation to achieve more optimal results. Contribution: This study contributes by evaluating the effectiveness of CV. Kopi Panas’s marketing strategies, which include product development, pricing review, diversification of event locations, promotion optimization, team skill development, process efficiency improvement, and physical facility maintenance. These strategies have enhanced the company’s brand visibility and market competitiveness. However, the findings also highlight the need for further adjustments in digital promotion and product innovation to achieve more optimal results.